Analysis of milkfish amplang business productivity in Sarijaya Village, Sanga-Sanga District, Kutai Kartanegara Regency - Satrio, Novan Donny; Haqiqiansyah , Gusti; Fahrizal, Wahyu (Jurnal Ilmu Perikanan Tropis Nusantara (Nusantara Tropical Fisheries Science Journal), 2024)
The purpose of this study is to determine the level of productivity of milkfish amplang business. This type of research is descriptive quantitative. The sample in this study was 4 respondents by sampling using the census method. The data analysis method uses business productivity analysis. The results showed that the level of fish productivity was 1.6 Kg which means that 1 Kg of milkfish was able to produce 1.6 Kg of amplang whereas, the level of labor productivity was 19.2 Kg / HKP which means that every 1 HKP of labor was able to produce 19.2 Kg of amplang